Quality protein maize story - Vasal, S. K. (International Food Policy Research Institute, 1999)
This paper is intended to present a critique of various aspects of protein related nutritional improvements in maize. Earlier efforts and difficulties in developing germplasm products that failed to meet expectations and lacked agronomic performance and acceptance at the farmer’s level will be discussed. Sequence of events will be presented that led to choosing an option and a strategy that turned out to be successful and has proved viable in developing a speciality corn type which is referred to as Quality Protein Maize (QPM).